Additional information for the interpretation of the practice of rural development in the light of the corporate relations of the Agricultural Centre, University of Debrecen in the North-Great Plain Region - Mohácsi, Márta (Acta Agraria Debreceniensis, 2008)
In the spirit of the Lisbon strategy, the European Union has set out the primary aims of innovation development and competitiveness. A potential method to reach these aims is to enhance the relation between science and practice and to apply scientific results. This is the case at the Agricultural Centre of the University of Debrecen as well, since the tighter and looser cooperations of the institution provide a scientific structure, which is now a significant prerequisite for Hungarian agro-innovation, primarily for rural development processes in the North Great Plain Region. The present study, based mostly on empirical findings, strives to analyze the field of activities in relation to rural development performed by the Agricultural Centre, University of Debrecen.